Composite antibacterial formaldehyde-removing difunctional coating and preparation method thereof

By combining amine-modified acrylic resin, modified bamboo charcoal powder, PDA@TiO2 photocatalyst, and nano silver paste, the problems of easy desorption of activated carbon and precipitation of antibacterial agents are solved, achieving efficient and stable formaldehyde removal and antibacterial effects, suitable for vehicle interiors and home building materials.

CN120966329APending Publication Date: 2025-11-18TAIZHOU VOCATIONAL & TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511077050.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

In existing antibacterial and formaldehyde-removing coatings, activated carbon is easily affected by temperature, leading to secondary formaldehyde release. Antibacterial agents are also prone to precipitation, affecting the effect. Furthermore, the low solar energy utilization rate and high electron-hole recombination rate of photocatalytic materials result in reduced catalytic activity.

Method used

A combination of amine-modified acrylic resin, modified bamboo charcoal powder, PDA@TiO2 photocatalyst, nano-silver paste, and quaternary ammonium salt dispersant is used to achieve stable decomposition and long-lasting sterilization of formaldehyde through a combination of chemical reaction and physical adsorption. The amide groups in the amine-modified acrylic resin react with formaldehyde to generate irreversible cyclic compounds of 2-imidazolidineone. PDA@TiO2 generates active oxygen under visible light to decompose formaldehyde, and silver ions are released through the nano-silver paste to destroy bacterial cell membranes.

Benefits of technology

It effectively reduces secondary formaldehyde release, improves antibacterial effect, achieves efficient formaldehyde removal and long-lasting sterilization, with a formaldehyde removal rate of >80%, an antibacterial rate of >99.9%, and good durability, with a formaldehyde removal rate decay of <10% after 500 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005529688100000011
    Figure FDA0005529688100000011
  • Figure FDA0005529688100000012
    Figure FDA0005529688100000012
Patent Text Reader

Abstract

The invention discloses a composite antibacterial formaldehyde-removing dual-functional coating and a preparation method thereof. The composite antibacterial formaldehyde-removing dual-functional coating is prepared from amido modified acrylic resin, waterborne epoxy resin, modified bamboo charcoal powder, a PDA-coated TiO2 photocatalyst, 2-imidazolidone, nano-silver colloid, a quaternary ammonium salt dispersing agent and auxiliaries. The formaldehyde is removed through combination of chemical reaction and physical adsorption, a stable hydroxymethyl compound can be generated through nucleophilic addition reaction of amide groups in the amino-modified acrylic resin and formaldehyde, and formaldehyde can be decomposed into CO2 and H2O through active oxygen generated under visible light by coating titanium dioxide with polydopamine. Therefore, secondary release of formaldehyde and secondary pollution can be reduced; formaldehyde can be efficiently adsorbed for a long time through pores through the modified bamboo charcoal powder; and sterilization can be realized in multiple ways.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of coating technology, and particularly relates to a composite antibacterial and aldehyde-removing bifunctional coating and a preparation method thereof. BACKGROUND

[0002] With the continuous improvement of human health consciousness, the quality of the environment where human beings live is also paid more and more attention. The pollution caused by bacteria and microorganisms in the environment and formaldehyde and toluene seriously threatens human physical and mental health. Antibacterial and aldehyde-removing coating can be directly coated on different materials, for example, coated on vehicle interiors or home building materials, effectively purifying the air and reducing the infection rate of bacteria. In order to realize the antibacterial function, inorganic antibacterial agents such as nano-silver and titanium dioxide are generally added in the coating; in order to realize the aldehyde-removing function, adsorbing materials such as activated carbon are generally added in the coating, but activated carbon is easily desorbed by temperature and releases harmful substances such as formaldehyde into the air, causing secondary pollution, and the antibacterial agent is easy to precipitate, affecting the antibacterial and aldehyde-removing effect of the coating, so it is necessary to improve the existing coating.

[0003] Titanium dioxide (TiO2) has been used for water splitting since its discovery in 1972, and has been booming in the past few decades due to its low cost, stable chemical and physical properties, and high specific area (Nature, 1972, 238). In recent years, with the full recognition of the harmfulness of formaldehyde by the medical community and the high attention of consumers to health, researchers have used these photocatalytic materials to generate electron-hole pairs under light conditions, thereby realizing the degradation of formaldehyde.

[0004] However, due to the wide band gap of most photocatalytic materials, the utilization rate of sunlight is low and the recombination rate of photo-generated electron-hole pairs is high, which further limits its application in improving indoor pollutants. Researchers have found that doping Ag nanoparticles can reduce the semiconductor band width, making it easier for excited electrons to be captured and slowing down the recombination rate of electron-hole pairs, thereby improving the utilization rate of visible light and the catalytic activity of photocatalytic materials (Nanomaterials, 2020, 10). In addition, nano-silver has excellent killing effect on E. coli, S. aureus, MRSA, influenza virus, etc., and is an ideal antibacterial agent (Laser Physics, 2020, 31). However, when the interaction between the metal and the carrier is weak, it is easy to separate and fall off during the catalytic reaction, causing a decrease in catalyst activity and stability. Therefore, how to stabilize the nanocomposite in the reaction system is a difficult problem. At the same time, in order to further enhance the effect of removing aldehyde, adsorbent materials such as activated carbon are generally added to the paint, but activated carbon is easily desorbed by temperature, releasing harmful substances such as formaldehyde back into the air, causing secondary pollution, and the antibacterial agent is easy to precipitate, affecting the antibacterial and aldehyde-removing effect of the paint, so it is necessary to improve the existing paint. SUMMARY

[0005] Therefore, based on the above background, the present application provides a composite antibacterial and aldehyde-removing bifunctional paint and a preparation method thereof.

[0006] The technical scheme provided by the present application is:

[0007] A composite antibacterial and aldehyde-removing bifunctional paint, which is made of the following raw materials by weight:

[0008] 45-60 parts of amine-modified acrylic resin;

[0009] 15-25 parts of water-based epoxy resin;

[0010] 8-15 parts of modified bamboo charcoal powder;

[0011] 3-5 parts of PDA@TiO2 photocatalyst;

[0012] 5-8 parts of 2-imidazolidone;

[0013] 2-3 parts of nano-silver glue;

[0014] 1-2 parts of quaternary ammonium salt dispersant;

[0015] 1.2-5 parts of auxiliary agent;

[0016] 10-30 parts of deionized water.

[0017] Further, the auxiliary agent includes a leveling agent 0.5-1.5 parts by weight, a defoaming agent 0.3-1.2 parts by weight, and an adhesion promoter 1-1.5 parts by weight.

[0018] Further, the raw materials for preparing the amine-modified acrylic resin include, by weight:

[0019] hydroxyethyl methacrylate 20-35 parts;

[0020] N-methylol acrylamide 10-25 parts;

[0021] butyl acrylate 30-55 parts;

[0022] ammonium persulfate 0.5-1.2 parts;

[0023] deionized water 30-55 parts.

[0024] Further, the preparation of the amine-modified acrylic resin includes the following steps:

[0025] ①Dissolve ammonium persulfate in deionized water, heat to 80℃, then add hydroxyethyl methacrylate, butyl acrylate, and N-methylol acrylamide in sequence;

[0026] ②Heat to 85±2℃ and keep the temperature for reaction;

[0027] ③After the reaction is completed, cool to 35-45℃, adjust the pH to 8.0 with ammonia water, filter the solid, and dry it.

[0028] Further, the modification of the modified bamboo charcoal powder includes the following steps:

[0029] 1) Take bamboo charcoal powder and silane coupling agent in a weight ratio of (10-12):(2-5), take silane coupling agent and anhydrous ethanol in a weight ratio of (0.5-2):(30-65), and take distilled water in an amount of 5-10 times the mass of the silane coupling agent;

[0030] 2) Crush the bamboo charcoal powder through a 80-120 mesh sieve to remove large particle impurities, then place it in an oven for drying treatment, with a drying temperature of 100-120℃ and a drying time of 2-3h;

[0031] 3) Mix water and anhydrous ethanol to obtain an ethanol aqueous solution, then add the silane coupling agent to the ethanol aqueous solution under stirring, continue stirring for 30-60min, and prepare a silane hydrolysis solution;

[0032] 4) Under stirring, spray the silane hydrolysis solution in step 3) onto the bamboo charcoal powder, continue stirring for 30-40min after spraying, and then vacuum dry.

[0033] Further, the preparation of the PDA@TiO2 photocatalyst comprises the following steps:

[0034] (1) dispersing TiO2 powder with a particle size of 22-80 nm in Tris-HCl buffer solution with a pH of 8.5;

[0035] (2) adding dopamine in an amount of 8-15% by weight of the TiO2 powder to the dispersion of step (1) and stirring for no less than 24 h;

[0036] (3) collecting the solid after centrifuging the reaction solution of step (2) and drying the solid.

[0037] Further, the preparation comprises the following steps:

[0038] S1: adding an amine-modified acrylic resin and a water-based epoxy resin into deionized water and stirring to disperse, to obtain a first dispersion;

[0039] S2: adding modified bamboo charcoal powder, 2-imidazolidone and a quaternary ammonium salt dispersant to the dispersion in step S1;

[0040] S3: adding nano-silver glue and PDA@TiO2 photocatalyst into water, ultrasonic treatment, to obtain a second dispersion, then slowly adding the second dispersion into the first dispersion, then stirring in the dark for 40-55 min, to obtain a mixture;

[0041] S4: sequentially adding a leveling agent, a defoaming agent and an adhesion promoter to the mixture of step S3, and stirring for 20-30 min.

[0042] Further, the adhesion promoter is selected from KH550 silane coupling agent.

[0043] Further, the leveling agent is selected from fluorocarbon type.

[0044] The above technical solutions have the following beneficial effects:

[0045] The aldehyde is removed by chemical reaction and physical adsorption, the amido group (-NHCO-) in the amido-modified acrylic resin reacts with formaldehyde to generate stable hydroxymethyl compounds through nucleophilic addition reaction, 2-imidazolidinone reacts with formaldehyde to generate irreversible cyclic compounds, and the active oxygen (·OH) is generated by the polydopamine-coated titanium dioxide (PDA@TiO2) under visible light to decompose formaldehyde into CO2 and H2O, so that the secondary release of formaldehyde can be reduced to cause secondary pollution; and the modified bamboo charcoal powder can adsorb formaldehyde for a long time through the porous and efficient adsorption; and the high-efficiency antibacterial effect is realized by combining contact antibacterial and photodynamic sterilization, the silver ions released from the nano-silver glue can destroy the bacterial cell membrane, and the quaternary ammonium salt dispersant can interfere with microbial metabolism to realize contact sterilization, and the active oxygen generated by the polydopamine-coated titanium dioxide (PDA@TiO2) under visible light can destroy the virus shell and bacterial DNA to realize sterilization, and can be more uniformly dispersed in the coating system and is not easy to precipitate, and long-acting sterilization can be realized. DETAILED DESCRIPTION

[0046] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be described below in connection with the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0047] Embodiment 1: A composite antibacterial and aldehyde-removing bifunctional coating, which is composed of the following raw materials by weight:

[0048] 55 parts of amido-modified acrylic resin;

[0049] 20 parts of water-based epoxy resin;

[0050] 12 parts of modified bamboo charcoal powder;

[0051] 5 parts of PDA@TiO2 photocatalyst;

[0052] 3 parts of 2-imidazolidinone;

[0053] 3 parts of nano-silver glue;

[0054] 2 parts of quaternary ammonium salt dispersant;

[0055] 3.2 parts of auxiliary agent;

[0056] 30 parts of deionized water.

[0057] The auxiliary agent includes 1.5 parts of leveling agent, 0.5 parts of defoaming agent and 1.2 parts of adhesion promoter by weight.

[0058] The adhesion promoter is selected from KH550 silane coupling agent.

[0059] The leveling agent is selected from fluorocarbon type.

[0060] The leveling agent is selected from Tego-450.

[0061] In this embodiment, the raw materials for preparing the amine-modified acrylic resin by weight include:

[0062] Hydroxyethyl methacrylate 25 parts;

[0063] N-methylol acrylamide 15 parts;

[0064] Butyl acrylate 55 parts;

[0065] Ammonium persulfate 50 parts.

[0066] Further, the preparation of the amine-modified acrylic resin includes the following steps:

[0067] ①Take ammonium persulfate and dissolve in deionized water, heat to 80℃, then add hydroxyethyl methacrylate, butyl acrylate, N-methylol acrylamide in turn;

[0068] ②Heat to 85±2℃, keep the reaction;

[0069] ③After the reaction is completed, cool to 35-45℃, adjust the pH to 8.0 with ammonia, filter, dry the filter solid, and it is ready.

[0070] In this embodiment, the modification of the modified bamboo charcoal powder includes the following steps:

[0071] 1) Take bamboo charcoal powder and silane coupling agent KH570 at a weight ratio of 10:2, take silane coupling agent and anhydrous ethanol at a weight ratio of 2:55, and take distilled water at 10 times the mass of the silane coupling agent;

[0072] 2) Crush the bamboo charcoal powder through an 80-120 mesh sieve, remove large particle impurities, and then place it in an oven for drying treatment, with a drying temperature of 100℃-120℃ and a drying time of 2-3h;

[0073] 3) First mix water and anhydrous ethanol to obtain an ethanol aqueous solution, then under stirring conditions, add the silane coupling agent to the ethanol aqueous solution, continue stirring for a period of time, and then prepare a silane hydrolysis solution;

[0074] 4) Under stirring conditions, spray the silane hydrolysis solution in step 3) onto the bamboo charcoal powder, continue stirring for 30-40min after spraying, and then vacuum dry.

[0075] In this embodiment, the preparation of the PDA@TiO2 photocatalyst comprises the following steps:

[0076] (1) dispersing 22-80nm TiO2 powder in Tris-HCl buffer solution with pH of 8.5;

[0077] (2) adding 10% of dopamine by weight of the TiO2 powder to the dispersion of step (1) and stirring for no less than 26h;

[0078] (3) collecting the solid after centrifugation of the reaction solution of step (2) and drying the solid.

[0079] The preparation of the coating of this embodiment comprises the following steps:

[0080] S1: adding amine-modified acrylic resin and water-based epoxy resin into deionized water and stirring to disperse, obtaining a first dispersion;

[0081] S2: adding modified bamboo charcoal powder, 2-imidazolidone and quaternary ammonium salt dispersant to the dispersion of step S1;

[0082] S3: adding nano-silver glue and PDA@TiO2 photocatalyst into water, ultrasonic treatment, obtaining a second dispersion, then slowly adding the second dispersion into the first dispersion, then stirring in the dark for 40-55min, obtaining a mixture;

[0083] S4: sequentially adding leveling agent, defoaming agent and adhesion promoter to the mixture of step S3, then stirring for 20-30min.

[0084] The performance of the coating of this embodiment is detected:

[0085] The formaldehyde removal rate is >80%(GB / T 34682-2017, initial concentration of formaldehyde 1.0±0.1mg / m 3 );

[0086] The antibacterial rate is >99.9%(ISO 22196-2011, Escherichia coli / Staphylococcus aureus);

[0087] Durability: the formaldehyde removal rate attenuation is <10% after 500h of accelerated aging (xenon lamp aging ASTM D4587).

[0088] The above describes the present application and its embodiments, which is not restrictive, and the actual structure is not limited thereto. In general, if a person skilled in the art is inspired thereby, without departing from the spirit of the present application, without creative design, similar structure and embodiments to the technical solution can be designed and belong to the protection scope of the present application.

Claims

1. A composite antibacterial and formaldehyde-removing dual-function coating, characterized in that, By weight, it is composed of the following raw materials: 45-60 parts of amine-modified acrylic resin; 2. The composite antibacterial and formaldehyde-removing dual-function coating according to claim 1, characterized in that, By weight, the additives include 0.5-1.5 parts of leveling agent, 0.3-1.2 parts of defoamer, and 1-1.5 parts of adhesion promoter.

3. The composite antibacterial and formaldehyde-removing dual-function coating according to claim 1, characterized in that, The raw materials for preparing the amino-modified acrylic resin, by weight, include:

4. The composite antibacterial and formaldehyde-removing dual-function coating according to claim 3, characterized in that, The preparation of the amine-modified acrylic resin includes the following steps: ① Dissolve ammonium persulfate in deionized water, heat to 80℃, and then add hydroxyethyl acrylate, butyl acrylate, and N-hydroxymethyl acrylamide in sequence; ②Raise the temperature to 85±2℃ and maintain the temperature for the reaction; ③ After the reaction is complete, cool to 35-45℃, adjust the pH to 8.0 with ammonia, filter, collect the filtrate, and dry it.

5. The composite antibacterial and formaldehyde-removing dual-function coating according to claim 1, characterized in that, The modification of the modified bamboo charcoal powder includes the following steps: 1) Take bamboo charcoal powder and silane coupling agent in a weight ratio of (10-12):(2-5), take silane coupling agent and anhydrous ethanol in a weight ratio of (0.5-2):(30-65), and take distilled water at 5-10 times the mass of silane coupling agent. 2) Crush the bamboo charcoal powder through an 80-120 mesh sieve to remove large particles and impurities, then place it in an oven for drying at a temperature of 100℃-120℃ for 2-3 hours. 3) First, water and anhydrous ethanol are mixed to obtain an ethanol-water solution. Under stirring, silane coupling agent is added to the ethanol-water solution and stirred for a period of time to prepare a silane hydrolysate. 4) Under stirring conditions, spray the silane hydrolysate from step 3) onto the bamboo charcoal powder. After spraying, continue stirring for 30-40 minutes, and then vacuum dry.

6. The composite antibacterial and formaldehyde-removing dual-function coating according to claim 1, characterized in that, The preparation of the PDA@TiO2 photocatalyst includes the following steps: (1) Disperse 22-80 nm TiO2 powder in Tris-HCl buffer solution with pH 8.5; (2) Add 8-15% by weight of dopamine of TiO2 powder to the dispersion of step (1) and stir for no less than 24 hours; (3) After centrifuging the reaction liquid from step (2), collect the solid and dry it.

7. A composite antibacterial and formaldehyde-removing dual-function coating according to any one of claims 1 to 6, characterized in that, Its preparation includes the following steps: S1: Add amine-modified acrylic resin and waterborne epoxy resin to deionized water and stir to disperse them to obtain the first dispersion; S2: Add modified bamboo charcoal powder, 2-imidazolidine ketone, and quaternary ammonium salt dispersant to the dispersion in step S1; S3: After adding nano-silver paste and PDA@TiO2 photocatalyst to water, ultrasonic treatment is performed to obtain a second dispersion. Then, the second dispersion is slowly added to the first dispersion, and then stirred in the dark for 40-55 minutes to obtain a mixed solution. S4: Add leveling agent, defoamer and adhesion promoter to the mixture in step S3 in sequence, and then stir for 20-30 minutes.

8. The composite antibacterial and formaldehyde-removing dual-function coating according to claim 7, characterized in that, The adhesion promoter is selected from KH550 silane coupling agent.

9. The composite antibacterial and formaldehyde-removing dual-function coating according to claim 7, characterized in that, The leveling agent is selected from fluorocarbon type.